Rice sheath rot: An emerging global threat — will biocontrol-driven omics be the gamechanger - Shraddha Bhaskar Sawant; Repudi Shalem Raju; S.R. Prabhukarthikeyan; Devanshu Dev; Prachi Singh; Debasis Mitra; Priya Bhargava; Abhijeet Ghatak; Utkarsh Chaturvedi; Manoj Kumar Yadav; Sudha Nandni; Anil Kumar Singh (Physiological and Molecular Plant Pathology, 2026)

Nitric oxide: A key player in plant defense against biotic stress - Devanshu Dev; Shraddha Bhaskar Sawant; Prince Kumar Gupta; Priya Bhargava; Prachi Singh; Sudha Nandni; Udit Nandan Mishra; Sankarganesh E.; Abhijeet Ghatak (Plant Science, 2026)

High-Throughput sequencing: A tool to curb banana diseases of quarantine importance - Prachi Singh; Priya Bhargava; Sawant Shraddha Bhaskar; Jeetu Narware; Sudha Nandni; Pitambara; Devanshu Dev (European Journal of Plant Pathology, 2025)

Microbiome: What if the next green revolution is microbial? - Shraddha Bhaskar Sawant; Debasis Mitra; Repudi Shalem Raju; Ingle Sagar Nandulal; S.R. Prabhukarthikeyan; Archana Dhole; Prachi Singh; Priya Bhargava; Devanshu Dev; Suresh Patil; A. Srinivasaraghvan; J.N. Srivastava; et al. (Physiological and Molecular Plant Pathology, 2025)

Thunderstorm detection from GPM IMERG rainfall: Climatology of dynamical and thermodynamical processes over India - Talukdar Sasanka; Kumari Priya; Krishna K. Osuri; Dev Niyogi (International Journal of Climatology, 2023)
This study aims to (i) prepare a premonsoon thunderstorms database, (ii) understand the thunderstorm frequency, duration and intensity and (iii) composite analysis of dynamic and thermodynamic processes related to thunderstorms over India. The thunderstorm associated rainfall varies across India. Hence, a percentile‐based approach is implemented with the integrated multi‐satellite retrievals for global precipitation measurement (IMERG) dataset at 0.1° resolution to identify thunderstorms for 2001–2021. The 93rd percentile appears to be better for thunderstorm detection, with a success ratio of 82% (642 events are confirmed out of 786 detected) in eastern India. Further analysis indicated that 84% of the detected thunderstorms in eastern and northeastern India are associated with lightning activity. Based on this long‐term (2001–2021) thunderstorm data, the highest frequency of thunderstorms (40–45 events·year −1 ) is observed over the western foothills of the Himalayas, the northeast region, and the west coast of Kerala. The thunderstorm duration in the eastern and northeastern regions and the southwest coast of India is mostly 0.5–2.5 h, producing heavy rainfall (>7 mm·h −1 ) due to more moisture content and stronger updrafts. The composite structure of thermodynamic indices exhibits significant spatial variations over India and can be used to differentiate the regions of high thunderstorm activity. The minimum (maximum) convective available potential energy (convective inhibition) value required for thunderstorm development is not uniform throughout the country. However, the composites of K index and total totals index during thunderstorms are mostly uniform. This study highlights the benefits of IMERG rainfall in thunderstorm detection over India and helps to understand the local forcings and the effect of thunderstorm activity on different sectors like aviation, agriculture and so forth.

Effect of persistent organic pollutants in patients with ischemic stroke and all stroke: A systematic review and meta-analysis - Priya Dev; Kamalesh Chakravarty; Manoj Pandey; Rakesh Ranjan; Mareena Cyriac; Vijaya Nath Mishra; Abhishek Pathak (Toxicology, 2023)

Critical review on biogeochemical dynamics of mercury (Hg) and its abatement strategies - Arun Dev Singh; Kanika Khanna; Jaspreet Kour; Shalini Dhiman; Tamanna Bhardwaj; Kamini Devi; Neerja Sharma; Pardeep Kumar; Nitika Kapoor; Priyanka Sharma; Priya Arora; Anket Sharma; et al. (Chemosphere, 2023)

Extension in the approaches to treat cancer through siRNA system: a beacon of hope in cancer therapy - Indra Rautela; Aditi Sharma; Pallavi Dheer; Priya Thapliyal; Shweta Sahni; Vimlendu Bhushan Sinha; Manish Dev Sharma (Drug Delivery and Translational Research, 2022)

Green diesel accomplishment through usage of feedstock and catalyst promising enhanced application for future prospective - Indra Rautela; Priya Thapliyal; Mohit Pant; Pallavi Dheer; Vimlendu Bhushan Sinha; Naveen Gaurav; Manish Dev Sharma (Arabian Journal of Geosciences, 2021)

Antioxidants and secondary metabolites changes in stomata and pollens of invasive alien plant Lantana camara - Priya Nischal; Arun Dev Sharma (Biologia, 2019)

Synthesis and in vitro anticancer activity of brevifoliol derivatives substantiated by in silico approach - Ranjeet Kaur; Sunil K. Chattopadhyay; Arnab Chatterjee; Om Prakash; Feroz Khan; Nitasha Suri; Dev Priya; A. K. Saxena (Medicinal Chemistry Research, 2014)